1999
DOI: 10.1002/(sici)1099-1409(199908/10)3:6/7<592::aid-jpp180>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis and Photocatalysis by Phthalocyanines for Technology, Ecology and Medicine

Abstract: This is a review of the recent studies done by the authors in the area of catalysis and photocatalysis by phthalocyanines and related compounds. Several examples of catalytic processes are given. Special attention is paid to the design of new types of photocatalytic systems for photodynamic therapy of cancer and to the development of novel catalytic methods of cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Antioxidants, as the name suggests are assumed as well as reported to be protective against damaging effect due to photo-oxidation (Jakus and Farkas, 2005;Stockert and Herkovits, 2003) yet sometimes the behavior may change for example in the presence of catalytic metals or at higher concentration they exhibit pro-oxidant activity (Jakus and Farkas, 2005;. In the case of PDT, some antioxidant molecules are reported to enhance the photodamaging effect of photosensitizer used in photodynamic therapy with various sensitizers and tumor models such as α-Tocopherol (Jakus and Farkas, 2005;Melnikova et al, 1999), Ascorbic acid (Bachowski et al, 1988;Buettner et al, 1993;Girotti et al, 1985;Jakus and Farkas, 2005;Kaliya et al, 1999;Kelley et al, 1997;Rosenthal and Ben-Hur, 1992), water-soluble vitamin E analog, Trolox (Jakus and Farkas, 2005;Melnikova et al, 2000) and BHA (Jakus and Farkas, 2005;. Therefore, few antioxidants can exaggerate the effects of photodynamic therapy with unknown mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants, as the name suggests are assumed as well as reported to be protective against damaging effect due to photo-oxidation (Jakus and Farkas, 2005;Stockert and Herkovits, 2003) yet sometimes the behavior may change for example in the presence of catalytic metals or at higher concentration they exhibit pro-oxidant activity (Jakus and Farkas, 2005;. In the case of PDT, some antioxidant molecules are reported to enhance the photodamaging effect of photosensitizer used in photodynamic therapy with various sensitizers and tumor models such as α-Tocopherol (Jakus and Farkas, 2005;Melnikova et al, 1999), Ascorbic acid (Bachowski et al, 1988;Buettner et al, 1993;Girotti et al, 1985;Jakus and Farkas, 2005;Kaliya et al, 1999;Kelley et al, 1997;Rosenthal and Ben-Hur, 1992), water-soluble vitamin E analog, Trolox (Jakus and Farkas, 2005;Melnikova et al, 2000) and BHA (Jakus and Farkas, 2005;. Therefore, few antioxidants can exaggerate the effects of photodynamic therapy with unknown mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, some studies have shown the combinational use of certain antioxidants can also enhance the activity of PDT, in which process antioxidants exhibit pro-oxidant activities, especially in the presence of catalytic metals 103. Several research groups have reported results on the PDT enhancing activities of certain antioxidant molecules, such as ascorbate,104 3(2)-tetra-butyl-4-hydroxyanisole,105 epigallocatechin-3-gallate,106 α-tocopherol,107 and trolox ([±]-6-hydroxyl-2, 5, 7, 8-tetramethyl chromane-2-carboxylic acid, a water soluble vitamin E analogue) 108. Based on these intriguing results, some antioxidant carrier sensitizers (ACSs) which conjugated PSs and antioxidants together were designed and studied for their photodynamic anticancer109 and antibacterial activities 110.…”
Section: Pdtmentioning
confidence: 99%
“…Heme is one of the most important biological catalysts, so this similarity suggests that phthalocyanines in general and FePc in particular might be excellent catalyst materials for oxidation and other chemical reactions. 4,[7][8][9][10][11] Indeed, phthalocyanines have, e.g., been employed in the cathodic oxygen dissociation in fuel cells. [12][13][14][15][16][17][18][19][20][21][22][23] However, under fuel cell standard conditions, i.e., using pure hydrogen as the feed, the activity of FePc remains below that of the widely used precious metal catalysts such as platinum.…”
Section: Introductionmentioning
confidence: 99%